2021
DOI: 10.1111/jcmm.16649
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypothermia in rat with acute myocardial ischaemia‐reperfusion injury complicating severe sepsis

Abstract: Myocardial ischemia‐reperfusion injury (MIRI) with concurrent severe sepsis has led to substantial mortality. Mild hypothermia (MHT) has been proved to have a therapeutic effect in either MIRI or severe sepsis, which suggests it might be beneficial for MIRI complicating severe sepsis. In this study, Sprague‐Dawley rats with MIRI complicating severe sepsis were allotted in either MHT (33 ± 0.5°C) group or normothermia (NT, 37 ± 0.5°C) group; as control, rats receiving sham surgery and normal saline were kept at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is considered that the investigation of the disease mechanism of MIRI can provide a novel concept for the development of therapeutic strategies for the treatment of this condition. Myocardial membrane permeability is increased in patients with MIRI, resulting in a rapid rise in LDH levels in the body ( 23 ). The results of the present study demonstrated that IL-32 levels were increased following H/R, whereas increased IL-32 levels promoted a cascade reaction in cardiomyocytes, which was accompanied by increased LDH release, inflammatory response, oxidative stress and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that the investigation of the disease mechanism of MIRI can provide a novel concept for the development of therapeutic strategies for the treatment of this condition. Myocardial membrane permeability is increased in patients with MIRI, resulting in a rapid rise in LDH levels in the body ( 23 ). The results of the present study demonstrated that IL-32 levels were increased following H/R, whereas increased IL-32 levels promoted a cascade reaction in cardiomyocytes, which was accompanied by increased LDH release, inflammatory response, oxidative stress and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…CS should be preheated to the desired temperature before being perfused into the cuvette to save time at later stages. Previous studies showed that mild hyperthermia (32–35°C) can protect myocardial tissue by increasing myocardial contractility and decreasing body metabolism 18–20 . Though these studies were conducted in vivo, lower temperature can also be applied on ex vivo myocardial tissues.…”
Section: Discussionmentioning
confidence: 99%